2016
DOI: 10.1111/jcmm.12948
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in pancreas of the Chinese giant salamander (Andrias davidianus)

Abstract: Telocytes (TCs), novel interstitial cells, have been identified in various organs of many mammals. However, information about TCs of lower animals remains rare. Herein, pancreatic TCs of the Chinese giant salamanders (Andrias davidianus) were identified by CD34 immunohistochemistry (IHC) and transmission electron microscopy (TEM). The IHC micrographs revealed CD34+ TCs with long telopodes (Tps) that were located in the interstitium of the pancreas. CD34+ TCs/Tps were frequently observed between exocrine acinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Our results clearly show the existence of long, convoluted, and moniliform Tps. Previous investigation showed that TCs are present in the pancreas of several mammals, cats, rats, degus, and humans [13,19,30,43]. In this study, we demonstrated the presence of TCs within the connective tissue in between the lobules and gland cells in the pancreas of Chinese soft-shelled turtles by TEM, IHC, and IF, according to the TC diagnostic criteria.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Our results clearly show the existence of long, convoluted, and moniliform Tps. Previous investigation showed that TCs are present in the pancreas of several mammals, cats, rats, degus, and humans [13,19,30,43]. In this study, we demonstrated the presence of TCs within the connective tissue in between the lobules and gland cells in the pancreas of Chinese soft-shelled turtles by TEM, IHC, and IF, according to the TC diagnostic criteria.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, TCs secrete extracellular vesicles that play an important role in supporting tissue repair/regeneration and nurse function, intercellular signaling, cell differentiation [16], homeostasis maintenance, and transport and release of lipids, proteins, as well as nucleic acids, in order to meet the target tissue requirements [17][18][19][20][21]. This communication is achieved by releasing the microRNA-filled extracellular vesicles from TCs/Tps to regulate cell functions [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations